Tourists behavioral intention to visit halal tourism destination: an empirical study on muslim tourists in Malaysia - Arije Ulfy, Mohammad; Haque, A. K. M. Ahasanul; Karim, Md Wasiul; Hossin, Md Suliman; Huda, Md. Nazmul (2021)
Today, the demand for halal tourism has increased dramatically and highlighted as one of the new horizons and fastest growing sector in the world’s tourism industry. Background Problem: Malaysia is indeed one of the countries with the most concerned halal segment in the tourism sector. Research Objective: The key purpose of this study is to examine the influence of affecting attributes on tourist’s behavioral intention to visit Malaysia as a halal tourism destination. Research Methods: The development of the research framework is based on the theory of plan behavior (TPB) model. A total of 394 responses were received from the Klang Valley area of Malaysia. For the purpose of analyzing the data, SPSS and AMOS was hired. Findings: Findings from the study reveal that, affecting attributes like, “Halal Certification for Food and Beverage”, “Destination Image” and “Emotional Incidents” have a significant positive influence on tourist’s satisfaction towards behavioral intention to determine the destination. Research Contribution: The key significance of this study demonstrated that a large number of Muslim travelers are able to experience Islamic cultures while considering halal tourism products and services in visiting accessible Muslim destinations. Conclusion: The conclusions of this research provided insights into the behavioral intentions of Muslim tourists select Malaysia as a destination for tourism.